2020
DOI: 10.1159/000506378
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin for the Early Prediction of Acute Kidney Injury in ST-Segment Elevation Myocardial Infarction Patients Treated with Primary Percutaneous Coronary Intervention

Abstract: Introduction and Objective: Neutrophil gelatinase-associated lipocalin (NGAL), a glycoprotein released by renal tubular cells, can be used as a marker of early tubular damage. We evaluated plasma NGAL level utilization for the identification of acute kidney injury (AKI) among ST-elevation myocardial infarction (STEMI) patients undergoing primary coronary intervention (PCI). Methods: 131 STEMI patients treated with PCI were prospectively included. Plasma NGAL levels were drawn prior to PCI (0 h) and 24 h afterw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…4 week post-MI, animals presented renal fibrosis, oxidative stress and inflammation. We show for the first time that these alterations were Several studies have demonstrated that MI is associated with renal damage (24,25). ER is an organelle essential for protein biosynthesis and post-translational modifications, which is very sensitive to unfolded and misfolded proteins in the lumen of ER.…”
Section: Discussionmentioning
confidence: 69%
“…4 week post-MI, animals presented renal fibrosis, oxidative stress and inflammation. We show for the first time that these alterations were Several studies have demonstrated that MI is associated with renal damage (24,25). ER is an organelle essential for protein biosynthesis and post-translational modifications, which is very sensitive to unfolded and misfolded proteins in the lumen of ER.…”
Section: Discussionmentioning
confidence: 69%
“…Optimal NGAL cutoffs previously reported in the literature to predict AKI were 142 ng/mL (EDTA plasma) and 148 ng/mL (heparin plasma) [7,10,11]. A previous study in PCI patients reported identification of AKI at NGAL ≥ 120 ng/mL according to the ROC curve [9]. NGAL levels > 100 ng/mL were found to be indicative of renal tubular damage in cardiac surgery patients [21].…”
Section: Discussionmentioning
confidence: 96%
“…Samples were taken to our facility's laboratory and centrifuged within 10 min using a cooled centrifuge. Plasma and serum were stored at -80 • C. NGAL levels were analyzed using NGAL rapid ELISA kits (Bioporto Diagnostics, Copenhagen, Denmark) [9][10][11]. The reagent kit includes immune-particle suspension and reaction buffers.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not clear whether this trend is observed following other operations. 6,7 The purpose of this study was to explore the value of serum PCT, CRP, and NGAL in the early diagnosis of AKI after UUTC, to provide a theoretical basis for reducing the risk of AKI and improving prognosis.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%